The Role of Work Stress as a Triggering Factor for Graves’ Disease - Adam, Riovani Nurfahmi; Ervano, Teddy; Alfian, Andi (Jurnal Indonesia Sosial Sains, 2025)
Graves’ disease is the most common form of autoimmune hyperthyroidism, characterized by excessive thyroid hormone production due to overstimulation of the thyroid-stimulating hormone receptor by autoantibodies (TRAb). Beyond genetic and immunological factors, psychosocial stress particularly chronic occupational stress plays a significant role in triggering and exacerbating the disease. Persistent activation of the hypothalamic pituitary adrenal (HPA) axis may cause immune dysregulation, contributing to the development of thyroid autoimmunity. A female patient working as a Head of the Accounting Division with a high workload presented with weight loss, palpitations, tremor, and insomnia. Laboratory evaluation revealed elevated T3 and FT4 levels, suppressed TSH, and positive TRAb. Thyroid ultrasonography showed diffuse gland enlargement consistent with diffuse toxic goitre. The patient was diagnosed with Graves’ disease and treated with thiamazole, propranolol, and alprazolam. Her perfectionist work style and chronic occupational stress were considered key triggers for sustained HPA axis activation and autoantibody formation. Numerous studies indicate that psychosocial stress increases the risk of Graves’ disease through complex neuroendocrine–immune interactions. Chronic HPA axis activation alters cortisol secretion and elevates proinflammatory cytokines such as IL-6 and TNF-α, leading to a loss of immune tolerance to thyroid tissue. This case underscores the importance of addressing psychosocial factors in the clinical evaluation and management of Graves’ disease. Chronic occupational stress may contribute to the onset and progression of Graves’ disease through neuroendocrine and immune dysregulation. Comprehensive management including pharmacologic therapy, stress reduction, psychosocial support, and workload adjustment is essential to achieve optimal remission and improve patients’ quality of life.